Pengaruh Partisipasi dan Diskresi terhadap Kualitas Pelayanan Publik pada Dinas Penanaman Modal dan Pelayanan Perizinan Terpadu Satu Pintu Kabupaten Bandung Barat (Studi Pelayanan Izin Lokasi dan Izin Mendirikan Bangunan) - Subagio, Bambang (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2020)
The public service quality in The Investment and One Stop Service (TIOSS) Office of Bandung Barat Regency was not optimal. The public participation and discretion were the crucial factors to improve the quality of the public service. Hence, this research examined the influence of the public participation and discretion factors to improve the public service quality in TIOSS Office of Bandung Barat Regency. This research used the mixed method. Quantitative method was reflected through survei technique data collection which then was analyzed through Structural Equation Model and Partial Least Square. While qualitative method was reflected through Focus Group Discussion technique. The results were, first, public participation and the discretion had a positive and significant impact to the public service quality. Second, the public participation variable partially had a greater effect than the discretion variable to improve the quality of the public service. The research suggested that TIOSS Office of Bandung Barat Regency should undertake synergic, comprehensive, and continuous of public participation and discretion practices in order to improve public service quality.